Time-Logic - Wu, Kuang-Ming (Scientific Research, 2017)
Time-logic is ever at work as story-logic in open coherence. This theme and its enormous significance, both sadly, totally, and usually neglected, are elucidated in this essay. This essay has five headings: time as not space, time-logic as not space-logic, matters are situation-dependent, story-logic in time-logic, and harmony in dissonance. In these five directions time-logic is etched forth impressively, surprisingly. Finally, these five sections are rounded up into an actual scene common and fresh.
Keywords: Logic; Time; Space; Situation; Concrete; Coherence; Child